1998
DOI: 10.1145/311106.311107
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting professional competence of information technology professionals

Abstract: Design and development of effective information technology (IT) based systems depends upon a staff of competent information technology professionals (ITPs). Due to the rapid pace of technological innovation, diverging application of IT, and changing role responsibilities of ITPs, it is becoming increasingly difficult for ITPs to maintain up-to-date professional competency.Although not extensively examined in IT research, professional obsolescence threats have been acknowledged and evaluated in referent researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The fear of obsolescence and the continual pressure to stay up-to-date through constant learning and retooling is an added stressor on top of an already demanding workload and tight deadlines (Mak & Sockel, 2001;Rajeswari & Anantharaman, 2003). Research in this area includes technical competence (Blanton, Schambach, & Trimmer, 1998), burnout (Moore, 2000), work stressors (Rajeswari & Anantharaman, 2003), and the impact of individual differences on performance in a changing environment (Gallivan, 2004).…”
Section: H S I N G -Y I T S a I D E B O R A H C O M P E A U A N Dmentioning
confidence: 99%
“…The fear of obsolescence and the continual pressure to stay up-to-date through constant learning and retooling is an added stressor on top of an already demanding workload and tight deadlines (Mak & Sockel, 2001;Rajeswari & Anantharaman, 2003). Research in this area includes technical competence (Blanton, Schambach, & Trimmer, 1998), burnout (Moore, 2000), work stressors (Rajeswari & Anantharaman, 2003), and the impact of individual differences on performance in a changing environment (Gallivan, 2004).…”
Section: H S I N G -Y I T S a I D E B O R A H C O M P E A U A N Dmentioning
confidence: 99%
“…People's attitudes towards their careers are usually manifested in their willingness to learn via formal courses or from the experiences gained by practice in the workplace. The company's attitude towards training -its "updating climate" -will also provide or prevent training opportunities [11]. However, it is the employee's personal attitude that will exploit learning opportunities or overcome obstacles that prevent them.…”
Section: Figure 2: a Socio-cognitive Frameworkmentioning
confidence: 99%
“…To take an example, many universities aspire to make greater use of technology-and resource-based learning, but such is the rate of technological change that some staff have such difficulty in maintaining up-to-date competencies that their outmoded knowledge and skills may actually prevent the full exploitation of the technology. Blanton, Schambach, and Trimmer (1998) stated that such obsolescence can be due to staff dispositions, a lack of training, a lack of intellectual and psychological challenge in the workplace, or an absence of those management practices, social influences, and reward systems that ensure an "updating climate" (p. 6). As far as staff disposition is concerned, Rogers (1983) showed that in every change, there will be "innovators," who advocate and lead new ideas and practices; "early adopters," who also demonstrate the possibility of change; an "early majority," who are cautious about…”
Section: What Does the Literature Say?mentioning
confidence: 99%